PUBLIC HEALTH UNDER PRESSURE: THE EFFECTS OF URBAN CONSTRUCTION PROJECTS IN KARACHI (Journal of Medical & Health Sciences Review, 2025)
Aims: To evaluate how the health of the local community in Karachi, Pakistan, is affected by ongoing constructive work.Methodology: A survey-based study was carried out with one thousand Karachi citizens. Interviews and questionnaires were used to gather data. The survey questionnaire included questions related to demographics, health outcomes, and exposure to constructive work.Result: The findings indicated a strong correlation between construction work and health consequences, including stress (45%), noise pollution (50%), and respiratory issues (55%). While 75% of respondents reported increased noise levels, the majority (80%) said that air quality had noticeably worsened since the construction began.Conclusion: The study comes to the conclusion that Karachi's residents' health is greatly impacted by ongoing construction work, especially when it comes to stress, noise pollution, and respiratory issues. To provide a healthy environment for residents and lessen the negative health effects of constructive work, immediate action is required.